Komparasi Kinerja Bank Mandiri dan Bank BCA Berdasarkan Rasio Profitabilitas - endang afriyeni; Raysa Amelia; Jumyetti Jumyetti; Novirwan Trinanto (Jurnal Ilmiah Poli Bisnis, 2019)
This study aims to compare the profitability of Bank Mandiri with BCA banks. they differ in ownership status and different amount of assets but are able to obtain almost the same profit. Using descriptive analysis because it is done to show and describe the state of the object of research related to profitability (measured by the ratio of GPM, NPM, ROA, ROE, BOPO, Rate of Return on Loans and Interest Expense Ratio) of the company. The objects of this study are Bank Mandiri and Bank BCA. The results of this study indicate that Bank BCA has better performance than Bank Mandiri based on profitability ratios. The best performance is shown by the ratio of NPM and BOPO.